ANALISIS MARKETING PENJUALAN PRODUK SEPATU COMPASS TERHADAP MINAT BELI KONSUMEN - Pramudya Elang Saputra (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study is to find out how to market the sales of Compass shoes. To find out how to promote shoe products by using influencers and selling online to consumers' buying points. The technique used is to collect data from the internet and analyze. Influencers and online sales have a very positive effect, thereby increasing consumer buying interest in compass shoes products